Concentric and Eccentric Endurance Exercise Reverse Hallmarks of T-Cell Senescence in Pre-diabetic Subjects - Philippe, Marc; Gatterer, Hannes; Burtscher, Martin; Weinberger, Birgit; Keller, Michael; Grubeck-Loebenstein, Beatrix; Fleckenstein, Johannes; Alack, Katharina; Krüger, Karsten (Frontiers in Physiology, 2019)
The peripheral T-cell pool undergoes a striking age associated remodeling which is accelerated by progressive insulin resistance. Exercise training is known to delay several aspects of T-cell senescence. The purpose of the current study was to investigate the effect of three weeks regular concentric or eccentric endurance exercise training on the composition of the T-cell compartment in pre-diabetic subjects. Sixteen male older adults with impaired glucose tolerance were recruited and performed either concentric (CE) or eccentric walking exercise (EE) 3 times a week for 3 weeks. Fasting venous blood sampling was performed before training and after the training intervention. Various T-cell subpopulations were analyzed by flow cytometry. We did not find significant time x group effects (interaction) but found several significant time effects for cell type ratios and cell subsets proportions. There was an increase of the CD4+/CD8+ (0.55±0.85%; p=0.033) and CD4+/CD3+ ratio (5.63±8.44%; p=0.018) and a decrease of the CD8+/CD3+ ratio (-0.95±1.64%; p=0.049) after training. We found proportional increases of CD4+/CCR7+/CD45RO+ central memory cells (5.02±7.68%; p=0.030), naïve CD8+/CCR7+/CD45RO- (3.00±6.68%; p=0.047) and CD8+/CCR7+/CD45RO+ central memory cells (3.01±3.70%; p=0.009), while proportions of CD4+/CCR7-/CD45RO- TEMRA cells (-2.17±4.66%; p=0.012), CD8+/CCR7-/CD45RO- TEMRA cells (-5.11±7.02%; p=0.018) and CD16+ cells (-4.67±6.45%; p=0.016) decreased after training. Three weeks of either CE or EE were effective in reversing hallmarks of T-cell senescence in pre-diabetic subjects. It is suggested that exercise stimulates production and mobilization of naïve T-cells, while differentiated TEMRA cells might disappear by apoptosis.